A Survey on the Duration of Leakage and Patient Perceived Bottlenecks to Seeking Fistula Treatment in Uganda - Asiimwe, Ian Shane; Matovu, Alphonsus (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Uganda still has high fistula burden with 75000-100000 women still living with obstetric fistula and yet new cases are being formed. The ministry of health together with supporting partners established regional treatment centers among which includes Hoima and Mubende regional referral hospitals. This aimed to assess the duration of leaking urine and patient perceived reasons for delay to seek repair among genitourinary fistula mothers who presented in fistula camps at Mubende and Hoima fistula treatment centers. Methods: This was a retrospective study in which qualitative and quantitative data was collected from standardized patient records of patient chats and registers filled by fistula surgeons. Results : We had a total of 125 mothers from 19 districts and of age between 16 to 72 years with genital urinary fistula operated. The majority (47.4%) of the clients were 25 years or less, of low parity with 41 % (para 1+0) and without formal employment. Only 59.5% of the clients presented within one year from the time they developed the fistula. Among the patient perceived bottlenecks are the perception that fistulas are only treated during camps, lack of money, ill health resulting from difficult labour and lack of awareness that the bladder can be repaired. Conclusions: With the low turn up of mothers seeking repair, there is need to reduce leaking time and lessen suffering of obstetric fistula patients by creating more awareness, promoting routine repairs and continued financial support to care for fistula clients.